Synthesis of substituted pyridine based sulphonamides as an antidiabetic agent - Sadawarte, Gautam; Jagatap, Samadhan; Patil, Mukesh; Jagrut, Vasant; Rajput, Jamatsing Darbarsing (European Journal of Chemistry, 2021)
This research work describes the synthesis of a new series of heterocyclic compounds, namely sulfonamide derivatives. Sulfonamides are a diverse class of organic compounds having significant and potent biological activities. Diverse synthetic methods have been engaged to build up its various derivatives for different biological functions. In this study, the production of novel pyridine-based heterocyclic compounds having sulfonamide moieties has been elaborated. The obtained sulfonamide-based pyridine scaffold was used to investigate their alpha-amylase inhibition activity. The structures of freshly prepared compounds were described using 1H NMR, 13C NMR, and IR spectroscopic techniques. The molecular docking of sulfonamides performed against porcine pancreatic alpha-amylase using PDB file 1LP was used for generation of grid. All the new synthesized compounds were shown notable anti-diabetic activity.